(x+1)(x+1)-16x*x=0

Simple and best practice solution for (x+1)(x+1)-16x*x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)(x+1)-16x*x=0 equation:


Simplifying
(x + 1)(x + 1) + -16x * x = 0

Reorder the terms:
(1 + x)(x + 1) + -16x * x = 0

Reorder the terms:
(1 + x)(1 + x) + -16x * x = 0

Multiply (1 + x) * (1 + x)
(1(1 + x) + x(1 + x)) + -16x * x = 0
((1 * 1 + x * 1) + x(1 + x)) + -16x * x = 0
((1 + 1x) + x(1 + x)) + -16x * x = 0
(1 + 1x + (1 * x + x * x)) + -16x * x = 0
(1 + 1x + (1x + x2)) + -16x * x = 0

Combine like terms: 1x + 1x = 2x
(1 + 2x + x2) + -16x * x = 0

Multiply x * x
1 + 2x + x2 + -16x2 = 0

Combine like terms: x2 + -16x2 = -15x2
1 + 2x + -15x2 = 0

Solving
1 + 2x + -15x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(1 + -3x)(1 + 5x) = 0

Subproblem 1

Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333

Subproblem 2

Set the factor '(1 + 5x)' equal to zero and attempt to solve: Simplifying 1 + 5x = 0 Solving 1 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = 0 + -1 5x = 0 + -1 Combine like terms: 0 + -1 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2

Solution

x = {0.3333333333, -0.2}

See similar equations:

| 3-abs(2x-1)=4 | | 13x-21=12x-24 | | 13x-21=12x-24 OK | | 5x+9=-46-3x | | 3=12/d | | 3x-3y-4-6x= | | 18X=750 | | -7=-12-x | | 6k^2-12k=0 | | 5x-1=4x+4 | | (x+1)(x+1)-16x*16x=0 | | 3(6-4)-4(7-9)= | | 3(x+10)=5x-4(6x-9)+38 | | 7x-10=9x+3 | | (144(x^12))^(1/2) | | 16-7x=264 | | 8x-5(x+1)=3x-5 | | 6(27)+7=7(27)-20 | | 3(2x^3)^1/2 | | (2senx-1)(2senx+1)=0 | | 7(5x-7)(3)-9.5=16 | | 4x-2ln(8)=ln(64) | | 5+log[5](5x)=6 | | 7-d=-12 | | 7(5x-7)=16 | | y-4=-2(x-1) | | 3/10=9/2x | | 2x/7-5=9 | | 3x^6+x^3-1=0 | | 6x+7=7x-20 | | log(x-3)=0.3 | | 1000=x^2/300^2 |

Equations solver categories